Sericin modulates learning and memory behaviors by tuning of antioxidant, inflammatory, and apoptotic markers in the hippocampus of aged mice - Seyedaghamiri, Fatemehsadat; Farajdokht, Fereshteh; Vatandoust, Seyed Mehdi; Mahmoudi, Javad; Khabbaz, Aytak; Sadigh-Eteghad, Saeed (Molecular biology reports, 2021)
Sericin is a protein derived from silkworm cocoons and identified as an anti-aging agent. This study aimed to examine the effects of sericin administration on episodic and avoidance memories, social interaction behavior, and molecular mechanisms including oxidative stress, inflammation, and apoptosis in the hippocampus of aged mice. Sericin was administered at 250 mg/kg/day (oral gavage) to 2-year-old BALB/c mice for a duration of 21 consecutive days. Lashley III Maze and Shuttle-Box tests were performed to assess episodic and avoidance memories, respectively. Subjects also underwent social interaction test to reveal any changes in their social behavior. Besides, markers of oxidative stress (TAC, SOD, GPx, and MDA) and neuroinflammation mediators (TNF-α, IL-1β, and IL-10) were measured in the hippocampus. The extent of apoptosis in the hippocampal tissue was further determined by TUNEL assay and histological assessment. The obtained results suggest that sericin promotes episodic and avoidance memories and social behaviors in aged mice. As of the molecular assay outcomes, it was noted that sericin regulates hippocampal inflammation by inhibiting the pro-inflammatory cytokines, TNF-α and IL-1β, and by increasing the anti-inflammatory factor IL-10. Moreover, sericin suppressed oxidative stress by enhancing antioxidant markers (TAC, SOD, and GPx) and inhibiting MDA. It was also identified that sericin can substantially suppress the apoptosis in the hippocampal tissue. Overall, sericin modulates memory and sociability behavior by tuning hippocampal antioxidant, inflammatory, and apoptotic markers in the aged mice.